KENAMPAKAN ANAK BULAN DI TELUK KEMANG: ANALISIS MENGIKUT PANDANGAN FIQH OLEH YUSUF AL-QARADAWI DAN PERSPEKTIF ASTRONOMI: Sighting of The New Moon at Teluk Kemang: An Analysis According to Fiqh’s View by Yusuf al-Qaradawi and from The Astronomical Perspective - Mohd Nawawi, Mohd Saiful Anwar; Abdul Niri, Mohammaddin; Zainuddin, Mohd Zambri (Jurnal Syariah, 2019)
This paper presents an analysis of the data of the visibility of the new moon collected at Teluk Kemang, Malaysia from 1972 to 2008. Contemporary fiqh’s views by Yusuf al-Qaradawi are employed as fundamental principles to scrutinize the data, that is, the use of calculation is more practical in achieving the legal objective of determining the visibility of new moon. The calculation should be used as a method to validate the report of new moon sighting. Based on the results obtained, we propose several geometrical parameters to be taken into consideration for sighting the new moon after sunset, such as the relative altitude at ≥ 5° and solar depression angle at ≥ 0.5°. According to the parameters, the minimum width of the new moon is visible to aided eyes on the 29th day of Hijri is 0.18 arc seconds. Based on fiqh’s consideration, we agree that the method of rukyah and istikmal used to determine the sighting of the new moon must be strengthened by using calculation in order to ensure that the sighting report is valid because of the possible occurrence of ambiguity and errors if that is the only method used.